Low-gram-weight anti-leakage PE film and preparation method thereof

By using nanoscale calcium carbonate and different types of PE resins, combined with three-layer casting coextrusion and microstretching processes, a low-grain weight and anti-leakage PE film was prepared, which solved the problems of traditional PE films with high weight and poor anti-leakage properties, and achieved a high-performance PE film.

CN119636207APending Publication Date: 2025-03-18FOSHAN YOUCAI NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411818846.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Traditional PE films have a high weight, resulting in a decrease in tensile strength and elongation of break. At the same time, the leakage resistance is not good, which cannot meet the market's demand for low-grain anti-leakage high-performance PE films.

Method used

A PE film mixture composed of mLLDPE resin, LLDPE resin, LDPE resin and nano-scale calcium carbonate is used to carry out three-layer casting coextrusion and micro-stretching processes through a twin-screw extruder to form an upper film layer, an intermediate film layer and a lower film layer to ensure the disorder of the distribution of nano-scale calcium carbonate and the misalignment of micropores, and enhance the leakage resistance.

Benefits of technology

On the premise of ensuring low gram weight, the PE film has obtained breathability, leakage resistance, suitable shrinkage, high tensile strength and high elongation of break to meet the product's use needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005182581530000161
    Figure BDA0005182581530000161
Patent Text Reader

Abstract

The invention discloses a low-gram-weight anti-leakage PE (polyethylene) film. The gram weight of the PE film is 26-28g / m < 2 >; the PE film comprises an upper film layer, a middle film layer and a lower film layer which are sequentially distributed from top to bottom, and the upper film layer, the middle film layer and the lower film layer are all obtained by melting, extruding, stretching and curing PE film mixed materials; the PE film mixture is prepared from the following raw materials in percentage by mass: mLLDPE resin, LLDPE resin, LDPE resin and nanoscale calcium carbonate, and the addition amount of the nanoscale calcium carbonate is 45-48%. According to the low-gram-weight anti-leakage PE film, on the premise that low gram weight is ensured, the low-gram-weight anti-leakage PE film has air permeability, anti-leakage performance, appropriate contractibility, high tensile strength and high elongation at break, and the defects in the prior art are overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of PE films, and in particular to a low-weight leakage-proof PE film and a preparation method thereof. Background Art

[0002] Polyethylene film (PE film) is a film produced by extrusion blow molding, extrusion calendering or extrusion casting of various types of PE resins and additives. Due to its anti-pollution, soft and comfortable, safe and non-toxic characteristics, in addition to being used as food packaging film, medical packaging film, pool film, waterproof film and agricultural film, it is also widely used as a base film in various sanitary products such as women's sanitary napkins, baby diapers and adult incontinence products.

[0003] With the continuous improvement of sanitary product technology and the increasing requirements of people for sanitary products, sanitary care products are gradually developing in the direction of "softer, more comfortable, and thinner", which puts higher requirements on PE film, one of the raw materials of sanitary products. Not only does it require PE film to have excellent anti-leakage performance to protect users from leakage, but it also requires PE film to have low gram weight to achieve thinness of sanitary products, so as to make sanitary products more close-fitting and improve wearing comfort while reducing raw material consumption and production costs. However, the gram weight of traditional PE film is usually 30g / m 2 As mentioned above, although its tensile strength and elongation at break are high, its gram weight is also high. Moreover, based on the manufacturing process and the selection of raw materials, its leakage is large, which cannot meet the market demand for low-gram weight, leakage-proof and high-performance PE film.

[0004] In order to overcome the defects of traditional PE film products, major PE film manufacturers have developed and manufactured low-weight, leak-proof, high-performance PE films to meet market demand. However, as the weight of PE films decreases, the tensile strength and elongation at break of the products also decrease; in addition, the leakage resistance of the products is still poor and cannot meet the use requirements of the products, making the low-weight, leak-proof, high-performance PE films used in sanitary products still mainly dependent on imports, which increases the production cost of high-quality sanitary products to a certain extent. Summary of the invention

[0005] One of the purposes of the present invention is to provide a low-weight and leak-proof PE film, which, while ensuring low weight, not only has air permeability and leak-proof properties, but also has suitable shrinkage, high tensile strength and high elongation at break, so as to overcome the shortcomings of the prior art.

[0006] The second object of the present invention is to provide a method for preparing a low-weight anti-leakage PE film, which has simple steps and strong operability, and ensures that the weight of the prepared PE film is as low as 26g / m 2, water vapor permeability ≥1500g / (㎡.24h), transverse tensile strength ≥2.5N / 25mm, longitudinal tensile strength ≥10N / 25mm, transverse elongation at break ≥200%, longitudinal elongation at break ≥150%, longitudinal heat shrinkage 3-6%. On the premise of ensuring low gram weight, it not only has air permeability and leakage prevention, but also has suitable shrinkage, high tensile strength and high elongation at break to meet the use requirements of the product.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] A low-weight anti-leakage PE film, the weight of the PE film is 26-28g / m 2 ; and the PE film comprises an upper film layer, a middle film layer and a lower film layer which are sequentially distributed from top to bottom, and the upper film layer, the middle film layer and the lower film layer are all obtained by melt-extruding the PE film mixture, stretching and solidifying;

[0009] The PE mixed material comprises the following raw materials: mLLDPE resin, LLDPE resin, LDPE resin and nano-scale calcium carbonate, and the addition amount of the nano-scale calcium carbonate is 45-48% calculated by mass percentage.

[0010] Furthermore, calculated by mass percentage, the PE mixture includes the following raw materials: 20-30% mLLDPE resin, 12-27% LLDPE resin, 8-10% LDPE resin and 45-48% nano-calcium carbonate.

[0011] Furthermore, the particle size of the nano-scale calcium carbonate is 200-700 nm.

[0012] Furthermore, the gram weights of the upper film layer, the middle film layer and the lower film layer are all the same.

[0013] A method for preparing a low-weight anti-leakage PE film, which is used to prepare the low-weight anti-leakage PE film, comprises the following steps:

[0014] S1. Mix mLLDPE resin, LLDPE resin, LDPE resin and nano-calcium carbonate in a uniform ratio to obtain a PE mixture;

[0015] S2. The PE mixture is added to a twin-screw extruder for melting, and is conveyed to the first flow channel, the second flow channel and the third flow channel of the die head cavity under heat preservation; the melt in the first flow channel, the second flow channel and the third flow channel is combined at the die lip of the die head and three-layer cast co-extrusion is performed, and then the first intermediate film material is formed by pressing the cast steel roller and the cast pressure roller; the first intermediate film material is subjected to matte treatment and cooled to obtain a second intermediate film material;

[0016] S3. The second intermediate film material is sequentially subjected to three-step preheating and three-step micro-stretching to obtain a third intermediate film material, wherein the third intermediate film material has a microporous structure;

[0017] S4. The third intermediate film material is subjected to heat setting treatment, cooling treatment and embossing treatment in sequence to obtain a fourth intermediate film material; the surface of the fourth intermediate film material is subjected to corona treatment, and a low-weight anti-leakage PE film is obtained after rolling.

[0018] Furthermore, in step S3, the specific method of the three-stage stepped preheating is: using preheating rollers to perform first-stage preheating, second-stage preheating and third-stage preheating on the second intermediate film material respectively, and the preheating temperature of the first-stage preheating is 75-80°C, the preheating temperature of the second-stage preheating is 81-85°C, and the preheating temperature of the third-stage preheating is 86-90°C.

[0019] Furthermore, in step S3, the specific method of the three-stage stepped micro-stretching is: using three stretching rollers with temperatures of 85-95°C to perform first-stage micro-stretching, second-stage micro-stretching and third-stage micro-stretching on the second intermediate film material that has undergone three-stage stepped preheating, and the stretching ratio of the first-stage micro-stretching is 1.1-1.2, the stretching ratio of the second-stage micro-stretching is 1.2-1.5, and the stretching ratio of the third-stage micro-stretching is 1.5-1.8.

[0020] Furthermore, in step S2, the temperature of the casting steel roller and the casting pressure roller are both 20-28°C, and the mutual pressing force between the casting steel roller and the casting pressure roller is 4-6 kg / cm 2 .

[0021] Furthermore, in step S4, the corona current of the corona treatment is 3-5A.

[0022] Furthermore, in step S3, the water vapor permeability of the low-weight anti-leakage PE film is ≥1500g / (㎡.24h), the transverse tensile strength is ≥2.5N / 25mm, the longitudinal tensile strength is ≥10N / 25mm, the transverse elongation at break is ≥200%, the longitudinal elongation at break is ≥150%, and the longitudinal heat shrinkage is 3-6%.

[0023] The technical solution provided by the present invention may include the following beneficial effects:

[0024] 1. Due to the disordered distribution of nano-scale calcium carbonate in the upper film layer, the middle film layer and the lower film layer, the micropores formed after micro-stretching of the upper film layer, the middle film layer and the lower film layer are partially or completely dislocated. Even if the micropores of any of the upper film layer, the middle film layer and the lower film layer are penetrated by liquids such as blood and water, the position of the micropores of the next film layer is difficult to coincide with the position of the micropores of the previous film layer penetrated due to the dislocated arrangement, thereby hindering the continued leakage of liquids such as blood and water, greatly reducing the risk of leakage of liquids such as blood and water, and further ensuring the leakage resistance of the PE film.

[0025] 2. The molecular structure of mLLDPE resin is tight, which can effectively prevent the leakage of blood or water; at the same time, the molecular chain of LLDPE resin is linear, but it usually contains fewer short branches or no long branches, so that LLDPE resin can also form a tight crystalline structure during processing, thereby effectively preventing the leakage of blood or water. In addition, the molecular chain of LDPE resin is shorter, and although its intermolecular force is weak, it can effectively prevent the leakage of blood or water. In addition, mLLDPE resin, LLDPE resin and LDPE resin all have good heat sealing properties, so that the upper film layer, the middle film layer and the lower film layer can be tightly combined to form a firm sealing structure, which can also effectively prevent the leakage of blood or water. Therefore, based on the above principles, this technical solution ensures that the obtained PE film has anti-leakage properties by optimizing the type of calcium carbonate, the structure of the PE film and the type of resin, and meets the extremely high requirements for the anti-leakage properties of the PE film.

[0026] 3. Due to the regular molecular chain structure of LLDPE resin and a certain amount of long chain branches, mLLDPE resin can shrink evenly when heated and has excellent heat shrinkage performance. Similarly, the molecular chain of LLDPE resin is linear, but it usually contains fewer short chain branches or no long chain branches, which also has certain heat shrinkage performance. Through the mutual cooperation of the two, the PE mixture added with mLLDPE resin and mLLDPE resin has suitable heat shrinkage performance, thereby giving the PE film obtained by processing the PE mixture suitable heat shrinkage performance. DETAILED DESCRIPTION

[0027] The technical solution provides a low-weight anti-leakage PE film, the weight of the PE film is 26-28g / m 2 ; and the PE film comprises an upper film layer, a middle film layer and a lower film layer which are sequentially distributed from top to bottom, and the upper film layer, the middle film layer and the lower film layer are all obtained by melt-extruding a PE mixture, stretching and solidifying it;

[0028] The PE film mixture comprises the following raw materials: mLLDPE resin, LLDPE resin, LDPE resin and nano-scale calcium carbonate, and the addition amount of the nano-scale calcium carbonate is 45-48% calculated by mass percentage.

[0029] In order to solve the technical problem that the PE film in the prior art cannot meet the use requirements, the present technical solution proposes a low-weight and leak-proof PE film, including an upper film layer, a middle film layer and a lower film layer distributed from top to bottom, and through innovations in the preparation process of PE and the formula of the PE film mixture, the obtained PE film is not only breathable and leak-proof while ensuring low weight, but also has suitable shrinkage, high tensile strength and high elongation at break to meet the use requirements of the product.

[0030] Specifically, in order to make the PE film have a microporous structure in the prior art, calcium carbonate particles are usually added to the PE mixture. Subsequently, a twin-screw extruder is used to perform melt extrusion and micro-stretching process to obtain the PE film. During the micro-stretching process, the PE film will be subjected to a directional external force, thereby generating stress. The above-mentioned stress is particularly concentrated around the calcium carbonate particles, resulting in the breakage or orderly slip of the molecular chains of the PE film around the calcium carbonate particles, which promotes the formation of micropores. That is, the prior art uses calcium carbonate particles as nucleation points to guide the formation of micropores during the stretching process. However, the formation of micropores is highly dependent on the size of the calcium carbonate particles. The micron-level or millimeter-level calcium carbonate particles used in the conventional technology, even under a single micro-stretching action, the micropores formed after stretching are also relatively large, which increases the risk of leakage. In addition, the existing PE film generally adopts a single-layer structure design. The single-layer structure design makes the PE film as a base film for sanitary products, and liquids such as blood and water are easy to leak, further exacerbating the leakage problem. Therefore, the PE film in this scheme cannot be designed based on the above principle.

[0031] In order to give the PE film the property of anti-leakage, the technical solution adds nano-scale calcium carbonate to the PE mixture formula. Since the particle size of nano-scale calcium carbonate is significantly smaller than the particle size of micron-scale or millimeter-scale calcium carbonate particles used in traditional technology, the size of the micropores formed on the PE film after micro-stretching is smaller. The reduction in the size of the micropores is conducive to greatly improving the anti-leakage performance of the PE film, reducing the leakage of liquids such as blood and water, thereby ensuring the anti-leakage performance of the PE film.

[0032] In addition, the technical solution also optimizes the structural design of the PE film, so that the PE film includes an upper film layer, a middle film layer and a lower film layer distributed in sequence from top to bottom. Due to the disordered distribution of nano-scale calcium carbonate in the upper film layer, the middle film layer and the lower film layer, the micropores formed after micro-stretching of the upper film layer, the middle film layer and the lower film layer are partially or completely staggered, so that even if the micropores of any layer of the upper film layer, the middle film layer and the lower film layer are penetrated by liquids such as blood and water, the position of the micropores of the next film layer is difficult to overlap with the position of the micropores of the previous penetrated film layer due to the staggered arrangement, thereby hindering the continued leakage of liquids such as blood and water, greatly reducing the risk of leakage of liquids such as blood and water, and further ensuring the anti-leakage property of the PE film.

[0033] Since the type of PE resin has a great influence on the anti-leakage property of the PE film, it is difficult to meet the extremely high anti-leakage property requirements of the PE film by only optimizing the type of calcium carbonate and the structure of the PE film. Therefore, the technical solution also optimizes the type of PE resin.

[0034] Specifically, the resin types of the PE film mixture include mLLDPE resin (metallocene linear low-density polyethylene resin), LLDPE resin (linear low-density polyethylene resin) and LDPE resin (low-density polyethylene resin). Among them, the molecular structure of mLLDPE resin is tight, which can effectively prevent the leakage of blood or water; at the same time, the molecular chain of LLDPE resin is linear, but it usually contains fewer short branches or no long branches, so that LLDPE resin can also form a tight crystalline structure during processing, thereby effectively preventing the leakage of blood or water. In addition, the molecular chain of LDPE resin is shorter, and although its intermolecular force is weak, it can effectively prevent the leakage of blood or water. In addition, mLLDPE resin, LLDPE resin and LDPE resin all have good heat sealing properties, so that the upper film layer, the middle film layer and the lower film layer can be tightly combined to form a firm sealing structure, which can also effectively prevent the leakage of blood or water. Therefore, based on the above principle, the technical solution ensures that the obtained PE film has anti-leakage properties by optimizing the type of calcium carbonate, the structure of the PE film and the type of resin, thereby meeting the extremely high requirements for the anti-leakage properties of the PE film.

[0035] Secondly, the PE film in the technical solution forms micropores due to stretching, and the micropores of the upper film layer, the middle film layer and the lower film layer are partially or completely staggered, but because the water vapor molecules are very small, they have the ability to diffuse through the micropores, so that even if the micropores are staggered, the water vapor molecules can still diffuse and migrate through these tiny pores, making the PE film breathable. In addition, although the micropores of the upper film layer, the middle film layer and the lower film layer are partially or completely staggered, there is still a certain connectivity between the above micropores, so that water vapor can pass through, which is also conducive to making the PE film breathable. Further, the technical solution limits the addition amount of nano-scale calcium carbonate in the PE mixture to 45-48%, increases the number of micropores in the PE film, and forms a small and dense microporous structure in the upper film layer, the middle film layer and the lower film layer, which is conducive to the diffusion and migration of water vapor, making the PE film breathable. That is, the technical solution cooperates with each other through the above three aspects to make the PE film breathable.

[0036] Again, mLLDPE resin has the characteristics of high crystallinity, high strength and good toughness, which gives the PE mixture extremely high tensile strength and high elongation at break; LLDPE resin has high strength and toughness, which gives the PE mixture high tensile strength and elongation at break; LDPE resin (low-density polyethylene resin) has excellent softness and toughness, which gives the PE mixture high elongation at break; nano-scale calcium carbonate particles have a small particle size and a large specific surface area, and the above characteristics allow it to be effectively closely combined with the PE resin matrix (such as mLLDPE resin, LLDPE resin and LDPE resin), and when nano-calcium carbonate is uniformly dispersed in the PE film, it can serve as a reinforcing phase to significantly improve the tensile strength and elongation at break of the PE film. Therefore, the technical solution, through the mutual cooperation of mLLDPE resin, LLDPE resin, LDPE resin and nano-scale calcium carbonate, makes the PE mixture have high tensile strength and high elongation at break, and gives the PE film high tensile strength and high elongation at break.

[0037] Finally, mLLDPE resin has a regular molecular chain structure and contains a certain amount of long chain branches, which enables mLLDPE resin to shrink evenly when heated and has excellent heat shrinkage performance. Similarly, the molecular chain of LLDPE resin is linear, but usually contains fewer short chain branches or no long chain branches, which also has certain heat shrinkage performance. Through the mutual cooperation of the two, the PE mixture added with mLLDPE resin and mLLDPE resin has suitable heat shrinkage performance, thereby giving the PE film obtained by processing the PE mixture suitable heat shrinkage performance, which not only allows the PE film to fit closely with other materials of the sanitary napkin when heated to form a stable structure and improve the stability and reliability of the product, but also avoids excessive heat shrinkage, which causes the PE film to shrink excessively during the heating process, resulting in deformation or wrinkles, affecting the appearance and use effect of the sanitary napkin.

[0038] It should be noted that the crystallinity of LLDPE resin and LDPE resin is much lower than that of mLLDPE resin, which can effectively make up for the defect that mLLDPE resin has a higher crystallinity, resulting in greater inter-molecular force and requires a higher temperature to melt it, resulting in poor processing performance of PE mixture, thereby making PE mixture have stronger processability.

[0039] In addition, LDPE resin has good flexibility and ductility, which helps the PE film to undergo larger deformation when subjected to external force without being easily broken or torn, thereby ensuring product integrity. In addition, nano-calcium carbonate can also improve the wear resistance and tear resistance of the PE film, increasing the durability of the PE film.

[0040] Further description, calculated by mass percentage, the PE mixture includes the following raw materials: 20-30% mLLDPE resin, 12-27% LLDPE resin, 8-10% LDPE resin and 45-48% nano-calcium carbonate.

[0041] This technical solution optimizes the proportion of each raw material in the PE mixture, which is conducive to giving full play to the performance of each raw material while reducing costs, and is conducive to achieving the best performance of the PE film, thereby improving the market competitiveness of the PE film.

[0042] Preferably, calculated by mass percentage, the PE mixture includes 25% mLLDPE resin, 20% LLDPE resin, 10% LDPE resin and 45% nano-scale calcium carbonate.

[0043] It is further described that the particle size of the nano-scale calcium carbonate is 200 to 700 nm.

[0044] By limiting the particle size of nano-calcium carbonate, it is not only beneficial to improve the dispersion of calcium carbonate in the PE film, making it less likely to agglomerate, thereby ensuring the formation of evenly dispersed, small and dense micropores, improving the anti-leakage and air permeability of the PE film, but also beneficial to improve the strength and toughness of the PE film, thereby improving the tear and rupture resistance of the PE film.

[0045] It is further described that the gram weights of the upper film layer, the middle film layer and the lower film layer are all the same.

[0046] By optimizing the weight of each film layer in the PE film, the thickness and density of each film layer are more evenly distributed, reducing the risk of deformation or rupture caused by uneven force. In addition, the same weight of each film layer is also conducive to simplifying the production process and reducing production difficulty and cost.

[0047] A method for preparing a low-weight anti-leakage PE film, which is used to prepare the low-weight anti-leakage PE film, comprises the following steps:

[0048] S1. Mix mLLDPE resin, LLDPE resin, LDPE resin and nano-calcium carbonate in a uniform ratio to obtain a PE mixture;

[0049] S2. The PE mixture is added to a twin-screw extruder for melting, and is conveyed to the first flow channel, the second flow channel and the third flow channel of the die head cavity under heat preservation; the melt in the first flow channel, the second flow channel and the third flow channel is combined at the die lip of the die head and three-layer cast co-extrusion is performed, and then the first intermediate film material is formed by pressing the cast steel roller and the cast pressure roller; the first intermediate film material is subjected to matte treatment and cooled to obtain a second intermediate film material;

[0050] S3. The second intermediate film material is sequentially subjected to three-step preheating and three-step micro-stretching to obtain a third intermediate film material, wherein the third intermediate film material has a microporous structure;

[0051] S4. The third intermediate film material is subjected to heat setting treatment, cooling treatment and embossing treatment in sequence to obtain a fourth intermediate film material; the surface of the fourth intermediate film material is subjected to corona treatment, and a low-weight anti-leakage PE film is obtained after rolling.

[0052] The technical solution also proposes a method for preparing a low-weight and leak-proof PE film. The preparation method is simple and easy to operate, ensuring that the obtained PE film is not only breathable and leak-proof while having a low weight, but also has suitable shrinkage, high tensile strength and high elongation at break to meet the use requirements of the product.

[0053] Specifically, in step S3, the second intermediate film material is subjected to three-stage step preheating and three-stage step micro-stretching. The step preheating can gradually increase the temperature of the second intermediate film material to avoid thermal stress caused by sudden temperature rise; at the same time, since it is difficult to form an ideal microporous structure by a single stretching, and the size and distribution uniformity of the micropores are poor, it is easy to affect the anti-leakage property of the PE film. Therefore, the technical solution optimizes the stretching process, that is, the stretching is performed by a three-stage step micro-stretching method, so that the microporous structure of the PE film can be gradually optimized, thereby forming smaller and more uniform micropores, and enhancing the anti-leakage property of the PE film. In addition, the three-stage step micro-stretching can also avoid the sudden concentration of stress caused by single-stage stretching, which leads to the risk of easy rupture or damage of the PE film.

[0054] It should be noted that the present technical solution can also utilize an automatic thickness gauge to measure the thickness and gram weight of the third intermediate film material, and feed the test results back to the control system. By pre-setting the control system, the extrusion gap of the die head is automatically adjusted to ensure the extrusion stability of the PE film.

[0055] Preferably, in step S1, the mixing weight of the PE mixture is ≤10Kg, and the mixing time is 0.8-1min, so as to further ensure uniform mixing and thus ensure the performance of each film layer.

[0056] Preferably, in step S2, the melting temperature of the twin-screw extruder is 200-210°C, the insulation temperature is 210-230°C, and the temperature of the die head is 230-250°C.

[0057] By limiting the above parameters, the temperature of the twin-screw extruder from melting to the die head is gradually increased, which is beneficial to ensure the fluidity of the PE mixture in the twin-screw extrusion and ensure the three-layer cast co-extrusion after the PE mixture is melted.

[0058] Preferably, in step S2, the temperature of the first flow channel is 245-255°C, the temperature of the second flow channel is 235-240°C, and the temperature of the third flow channel is 245-255°C.

[0059] In a preferred embodiment of the present technical solution, by setting the temperature of the first flow channel and the third flow channel higher than the temperature of the second flow channel, that is, the temperature on both sides of the die cavity is higher than the temperature in the middle, the first mixture and the second mixture can flow more smoothly after melting, ensuring three-layer cast co-extrusion.

[0060] Preferably, in step S4, the temperature of the heat setting treatment is 100-110°C; the temperature of the cooling treatment is 25-35°C.

[0061] By limiting the temperature of the heat setting treatment, it is helpful to ensure the stability of the size and shape of the PE film.

[0062] Further explanation, in step S3, the specific method of the three-stage stepped preheating is: use preheating rollers to perform first-stage preheating, second-stage preheating and third-stage preheating on the second intermediate film material respectively, and the preheating temperature of the first-stage preheating is 75-80°C, the preheating temperature of the second-stage preheating is 81-85°C, and the preheating temperature of the third-stage preheating is 86-90°C.

[0063] By limiting the preheating temperatures of the first stage preheating, the second stage preheating and the third stage preheating, the second intermediate film material gradually reaches a temperature range suitable for stretching, avoiding thermal stress concentration and uneven stretching caused by sudden temperature rise, which is more conducive to ensuring product performance.

[0064] To further illustrate, in step S3, the specific method of the three-stage stepped micro-stretching is: using three stretching rollers with temperatures of 85-95°C to perform first-stage micro-stretching, second-stage micro-stretching and third-stage micro-stretching on the second intermediate film material that has undergone three-stage stepped preheating, and the stretching ratio of the first-stage micro-stretching is 1.1-1.2, the stretching ratio of the second-stage micro-stretching is 1.2-1.5, and the stretching ratio of the third-stage micro-stretching is 1.5-1.8.

[0065] The temperature of the stretching roller is set in the range of 85-95°C, which matches the temperature of the second intermediate film material after three-stage step preheating, ensuring that the second intermediate film material is in the best thermoplastic state during the stretching process, thereby facilitating the stretching effect.

[0066] In addition, by limiting the stretching ratio at each stage and increasing the stretching ratio step by step, the second intermediate film material that has undergone three-stage step preheating gradually reaches the desired orientation state during the stretching process, avoiding film rupture or performance degradation caused by sudden stretching, which is beneficial to ensuring the performance of the final PE film.

[0067] It should be noted that the stretching ratio refers to the ratio of the size of the film after stretching to the size of the film before stretching.

[0068] Further, in step S2, the temperature of the casting steel roller and the casting pressure roller are both 20-28°C, and the mutual pressing force between the casting steel roller and the casting pressure roller is 4-6 kg / cm 2 .

[0069] During the cooling and shaping process, the temperature of the cooling water is 25°C. When the temperatures of the casting steel roller and the casting pressure roller are both less than 20°C, the temperature is too low, and the cooling water is easy to condense on the first intermediate film material, affecting the subsequent processing of the first intermediate film material. When the temperatures of the casting steel roller and the casting pressure roller are both greater than 28°C, the temperature is too high, causing the first intermediate film material to be brittle and difficult to shape.

[0070] Furthermore, the mutual pressing force between the casting steel roller and the casting pressure roller is 4-6 kg / cm 2 , ensuring that each film layer can be pressed into shape.

[0071] Further description, in step S4, the corona current of the corona treatment is 3-5A.

[0072] Since sanitary products are composed of a surface layer, an absorbent core and a bottom film, and the PE film as the bottom film of the sanitary products needs to be bonded to the surface layer, so as to wrap the absorbent core between the surface layer and the bottom film. Therefore, the technical solution limits the corona current of the corona treatment to 3-5A, so that the surface tension of the PE film reaches 36-42mN / m, which facilitates the adhesion between the PE film as the bottom film of the sanitary products and the surface layer, and ensures the performance of the PE film.

[0073] Further description, in step S3, the water vapor permeability of the low-weight anti-leakage PE film is ≥1500g / (㎡.24h), the transverse tensile strength is ≥2.5N / 25mm, the longitudinal tensile strength is ≥10N / 25mm, the transverse elongation at break is ≥200%, the longitudinal elongation at break is ≥150%, and the longitudinal heat shrinkage is 3-6%.

[0074] The PE film obtained by the present technical scheme has a water vapor permeability of ≥1500g / (㎡.24h).24h, a transverse tensile strength of ≥2.5N / 25mm, a longitudinal tensile strength of ≥10N / 25mm, a transverse elongation at break of ≥200%, a longitudinal elongation at break of ≥150%, and a longitudinal heat shrinkage of 3-6%. On the premise of ensuring low gram weight, the film not only has air permeability and leakage prevention properties, but also has suitable shrinkage, high tensile strength and high elongation at break, thus meeting the use requirements of the product.

[0075] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0076] Performance Test:

[0077] Gram weight: Stack 10 layers of PE film, use a cutting board with a size of 100mm×100mm (i.e., the length and width are both 100mm, the same below) to cut 10 layers of test samples with an area of ​​0.01 (㎡.24h), and obtain a test sample with a total area of ​​0.1 (㎡.24h). Use an electronic balance to weigh the test sample, and then multiply the test result by 10 to obtain the gram weight.

[0078] Heat shrinkage performance: A test sample with a size of 100mm×100mm was cut from the middle and both sides of the film, and a total of 3 test samples were obtained. The initial length L0 of the three test samples in the longitudinal direction was measured and recorded respectively; the three test samples were placed in a constant temperature blast drying oven at a temperature of 60°C for 60 minutes, taken out and placed at room temperature for 30 minutes; then, the longitudinal mark length L1 of the three test samples after cooling was measured and recorded again; according to the formula: △ L=(L1-L0) / L0*100 Calculate the thermal shrinkage rate of each test sample, and take the average thermal shrinkage rate of three test samples as the final test result.

[0079] Air permeability: Cut a test sample of 100mm×100mm, inject 30ml of distilled water into the breathable cup, and weigh the initial weight M0 of the breathable cup filled with distilled water; place the breathable cup filled with distilled water in an environment with a temperature of 40℃ and a relative humidity of 50%, then place the test sample on the mouth of the breathable cup filled with distilled water and tighten and fix the test sample with a matching aluminum ring, measure the weight M1 of the breathable cup filled with distilled water after testing for a period of time, and calculate the water vapor permeability according to the formula: water vapor permeability = (M1-M0)×24 / (cup mouth area×test time), where the test time is in hours.

[0080] Elongation at break: The elongation at break is determined according to the test method of GB / T 1040.2-2006 Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics.

[0081] Elastic modulus: The elastic modulus is determined according to the test method of GB / T 1040.2-2006 Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics.

[0082] Leakage resistance: Take a group of test samples with a size of 100mm×100mm at intervals along the width direction of the film, and if the width of the film is ≤1500mm, take 5 samples; if the width is >1500mm, take 8 samples; Place a filter paper with a diameter of 70mm flat on the table, and then place the test sample in the center of the filter paper. Then, place another filter paper with a diameter of 70mm on top of the test sample; Use a pipette to accurately measure 1mL of the prepared 0.2wt% Congo red aqueous solution, and drop it in the center of the upper filter paper and let it stand for 1min; Press an acrylic plate with a size of 60mm×60mm×5mm (i.e., the length and width are both 60mm, and the thickness is 5mm) on the surface of the filter paper, and apply an additional weight of 200 grams on the acrylic plate and let it stand for 1min; After the test, remove the test sample and all upper coverings. If no red marks are found on the lower filter paper, the test sample is judged to be qualified for leakage resistance. The leakage resistance of the PE film can be judged as qualified only when all test samples in a group meet this standard.

[0083] Example 1

[0084] S1. 25% mLLDPE resin, 20% LLDPE resin, 10% LDPE resin and 45% nano-calcium carbonate having a particle size of 400nm were uniformly mixed to obtain a PE mixture weighing 10kg;

[0085] S2. Add the PE mixture into a twin-screw extruder at a temperature of 200-210°C to melt, and convey it to the first flow channel at a temperature of 250°C, the second flow channel at a temperature of 235°C and the third flow channel at a temperature of 250°C in the die head cavity at a temperature of 210-230°C; the molten liquid in the first flow channel, the second flow channel and the third flow channel are combined at the die lip of the die head at a temperature of 240°C and three-layer cast co-extruded, and then the first intermediate film material is formed by pressing the cast steel roller and the cast pressure roller; the first intermediate film material is subjected to matte treatment and cooled to obtain the second intermediate film material; wherein, the temperature of the cast steel roller and the cast pressure roller are both 25°C, and the mutual pressing force between the cast steel roller and the cast pressure roller is 5kg / cm 2 ;

[0086] S3. The second intermediate film material is sequentially subjected to three-stage step preheating and three-stage step micro-stretching to obtain a third intermediate film material, and the third intermediate film material has a microporous structure; wherein the specific method of the three-stage step preheating is: the second intermediate film material is respectively subjected to the first stage preheating, the second stage preheating and the third stage preheating by using preheating rollers, and the preheating temperature of the first stage preheating is 78°C, the preheating temperature of the second stage preheating is 82°C, and the preheating temperature of the third stage preheating is 88°C; the specific method of the three-stage step micro-stretching is: the second intermediate film material subjected to the three-stage step preheating is respectively subjected to the first stage micro-stretching, the second stage micro-stretching and the third stage micro-stretching by using three stretching rollers each having a temperature of 88°C, and the stretching ratio of the first stage micro-stretching is 1.2, the stretching ratio of the second stage micro-stretching is 1.5, and the stretching ratio of the third stage micro-stretching is 1.8;

[0087] S4. The third intermediate film material is subjected to heat setting treatment, cooling treatment and embossing treatment in sequence to obtain a fourth intermediate film material; the surface of the fourth intermediate film material is subjected to corona treatment, and a low-weight, leak-proof PE film is obtained after rolling; wherein the weights of the upper film layer, the middle film layer and the lower film layer are the same; the temperature of the heat setting treatment is 100°C; the temperature of the cooling treatment is 25°C; and the corona current of the corona treatment is 4A.

[0088] Example 2

[0089] S1. 30% mLLDPE resin, 15% LLDPE resin, 9% LDPE resin and 46% nano-calcium carbonate having a particle size of 300nm were uniformly mixed to obtain a PE mixture weighing 10kg;

[0090] S2. Add the PE mixture into a twin-screw extruder at a temperature of 200°C to melt, and convey it to the first flow channel at a temperature of 245°C, the second flow channel at a temperature of 235°C and the third flow channel at a temperature of 245°C in the die head cavity at a temperature of 220°C; the molten liquid in the first flow channel, the second flow channel and the third flow channel are combined at the die lip of the die head at a temperature of 230°C and three-layer cast co-extruded, and then the first intermediate film material is formed by pressing the cast steel roller and the cast pressure roller; the first intermediate film material is subjected to matte treatment and cooled to obtain the second intermediate film material; wherein, the temperature of the cast steel roller and the cast pressure roller are both 20°C, and the mutual pressing force between the cast steel roller and the cast pressure roller is 4kg / cm 2 ;

[0091] S3. The second intermediate film material is sequentially subjected to three-stage step preheating and three-stage step micro-stretching to obtain a third intermediate film material, and the third intermediate film material has a microporous structure; wherein the specific method of the three-stage step preheating is: the second intermediate film material is respectively subjected to the first stage preheating, the second stage preheating and the third stage preheating by using preheating rollers, and the preheating temperature of the first stage preheating is 77°C, the preheating temperature of the second stage preheating is 81°C, and the preheating temperature of the third stage preheating is 86°C; the specific method of the three-stage step micro-stretching is: the second intermediate film material subjected to the three-stage step preheating is respectively subjected to the first stage micro-stretching, the second stage micro-stretching and the third stage micro-stretching by using three stretching rollers each having a temperature of 86°C, and the stretching ratio of the first stage micro-stretching is 1.1, the stretching ratio of the second stage micro-stretching is 1.3, and the stretching ratio of the third stage micro-stretching is 1.5;

[0092] S4. The third intermediate film material is subjected to heat setting treatment, cooling treatment and embossing treatment in sequence to obtain a fourth intermediate film material; the surface of the fourth intermediate film material is subjected to corona treatment, and a low-weight, leak-proof PE film is obtained after rolling; wherein the weights of the upper film layer, the middle film layer and the lower film layer are the same; the temperature of the heat setting treatment is 105°C; the temperature of the cooling treatment is 30°C; and the corona current of the corona treatment is 3A.

[0093] Example 3

[0094] S1. 26% mLLDPE resin, 21% LLDPE resin, 8% LDPE resin and 45% nano-calcium carbonate having a particle size of 600nm were uniformly mixed to obtain a PE mixture weighing 10kg;

[0095] S2. Add the PE mixture into a twin-screw extruder at a temperature of 200°C to melt, and convey it to the first flow channel at a temperature of 255°C, the second flow channel at a temperature of 240°C and the third flow channel at a temperature of 255°C in the die head cavity at a temperature of 220°C; the molten liquid in the first flow channel, the second flow channel and the third flow channel are combined at the die lip of the die head at a temperature of 248°C and three-layer cast co-extruded, and then the first intermediate film material is formed by pressing the cast steel roller and the cast pressure roller; the first intermediate film material is subjected to matte treatment and cooled to obtain the second intermediate film material; wherein, the temperature of the cast steel roller and the cast pressure roller are both 25°C, and the mutual pressing force between the cast steel roller and the cast pressure roller is 5kg / cm 2 ;

[0096] S3. The second intermediate film material is sequentially subjected to three-stage step preheating and three-stage step micro-stretching to obtain a third intermediate film material, and the third intermediate film material has a microporous structure; wherein the specific method of the three-stage step preheating is: the second intermediate film material is respectively subjected to the first stage preheating, the second stage preheating and the third stage preheating by using preheating rollers, and the preheating temperature of the first stage preheating is 78°C, the preheating temperature of the second stage preheating is 83°C, and the preheating temperature of the third stage preheating is 89°C; the specific method of the three-stage step micro-stretching is: the second intermediate film material subjected to the three-stage step preheating is respectively subjected to the first stage micro-stretching, the second stage micro-stretching and the third stage micro-stretching by using three stretching rollers each having a temperature of 86°C, and the stretching ratio of the first stage micro-stretching is 1.2, the stretching ratio of the second stage micro-stretching is 1.4, and the stretching ratio of the third stage micro-stretching is 1.6;

[0097] S4. The third intermediate film material is subjected to heat setting treatment, cooling treatment and embossing treatment in sequence to obtain a fourth intermediate film material; the surface of the fourth intermediate film material is subjected to corona treatment, and a low-weight, leak-proof PE film is obtained after rolling; wherein the weights of the upper film layer, the middle film layer and the lower film layer are the same; the temperature of the heat setting treatment is 100-110°C; the temperature of the cooling treatment is 25-35°C, and the corona current of the corona treatment is 3-5A.

[0098] Comparative Example 1

[0099] The preparation method and raw materials of Comparative Example 1 are the same as those of Example 1, except that micron-sized calcium carbonate with a particle size of 2 um is used in the PE mixture formula of Comparative Example 1.

[0100] Comparative Example 2

[0101] The preparation method and raw materials of Comparative Example 2 are the same as those of Example 1, except that a single-layer membrane structure is used in Comparative Example 2.

[0102] Comparative Example 3

[0103] The preparation method and raw materials of Comparative Example 3 are the same as those of Example 1, except that single stretching is used in Comparative Example 3.

[0104] The PE films prepared in the above examples and comparative examples were subjected to performance tests, and the specific test results are shown in Table 1 below:

[0105] Table 1 PE film related performance test results

[0106]

[0107] From the performance test results of each embodiment in the above table, it can be seen that the PE film prepared by the method for preparing a low-weight anti-leakage PE film has a gram weight as low as 26g / m 2, water vapor permeability ≥1500g / (㎡.24h), transverse tensile strength ≥2.5N / 25mm, longitudinal tensile strength ≥10N / 25mm, transverse elongation at break ≥200%, longitudinal elongation at break ≥150%, longitudinal heat shrinkage 3-6%. Under the premise of ensuring low gram weight, it not only has air permeability and leakage prevention, but also has suitable shrinkage, high tensile strength and high elongation at break, which can meet the use requirements of the product.

[0108] In Comparative Example 1, due to the use of micron-sized calcium carbonate, its anti-leakage performance, tensile strength and elongation at break all decreased, and its air permeability increased.

[0109] Since Comparative Example 2 adopts a single-layer membrane structure, its anti-leakage performance, tensile strength and elongation at break are all reduced, and its air permeability is increased.

[0110] Since Comparative Example 3 adopts single stretching, it is difficult to form an ideal microporous structure, and the size and distribution uniformity of the micropores are poor. At the same time, the obtained PE film is prone to stress concentration, resulting in a decrease in its anti-leakage property, tensile strength, air permeability and elongation at break.

[0111] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.

Claims

1. A low-weight anti-leakage PE film, characterized in that: The gram weight of the PE film is 26-28 g / m 2 ; and the PE film comprises an upper film layer, a middle film layer and a lower film layer which are sequentially distributed from top to bottom, and the upper film layer, the middle film layer and the lower film layer are all obtained by respectively melt-extruding the PE film mixture, stretching and solidifying; The PE film mixture comprises the following raw materials: mLLDPE resin, LLDPE resin, LDPE resin and nano-scale calcium carbonate, and the addition amount of the nano-scale calcium carbonate is 45-48% calculated by mass percentage.

2. A low-weight anti-leakage PE film according to claim 1, characterized in that: Calculated by mass percentage, the PE film mixture comprises the following raw materials: 20-30% mLLDPE resin, 12-27% LLDPE resin, 8-10% LDPE resin and 45-48% nano-scale calcium carbonate.

3. A low-weight anti-leakage PE film according to claim 1, characterized in that: The particle size of the nano-scale calcium carbonate is 200-700 nm.

4. A low-weight anti-leakage PE film according to claim 1, characterized in that: The upper film layer, the middle film layer and the lower film layer have the same gram weight.

5. A method for preparing a low-weight anti-leakage PE film, characterized in that: The method for preparing the low-weight anti-leakage PE film as claimed in claims 2 to 4 comprises the following steps: S1. The mLLDPE resin, LLDPE resin, LDPE resin and nano-calcium carbonate are uniformly mixed to obtain a PE film mixture; S2. The PE film mixture is added to a twin-screw extruder for melting, and is conveyed to the first flow channel, the second flow channel and the third flow channel of the die head cavity under heat preservation; the melt in the first flow channel, the second flow channel and the third flow channel is combined at the die lip of the die head and three-layer cast co-extruded, and then the first intermediate film material is formed by pressing the cast steel roller and the cast pressure roller; the first intermediate film material is subjected to matte treatment and cooled to obtain a second intermediate film material; S3. The second intermediate film material is sequentially subjected to three-step preheating and three-step micro-stretching to obtain a third intermediate film material, wherein the third intermediate film material has a microporous structure; S4. The third intermediate film material is subjected to heat setting treatment, cooling treatment and embossing treatment in sequence to obtain a fourth intermediate film material; the surface of the fourth intermediate film material is subjected to corona treatment, and a low-weight anti-leakage PE film is obtained after rolling.

6. The method for preparing a low-weight anti-leakage PE film according to claim 5, characterized in that: In step S3, the specific method of the three-stage stepped preheating is: use preheating rollers to perform first-stage preheating, second-stage preheating and third-stage preheating on the second intermediate film material respectively, and the preheating temperature of the first-stage preheating is 75-80°C, the preheating temperature of the second-stage preheating is 81-85°C, and the preheating temperature of the third-stage preheating is 86-90°C.

7. The method for preparing a low-weight leakage-proof PE film according to claim 5, characterized in that: In step S3, the specific method of the three-stage stepped micro-stretching is: using three stretching rollers with temperatures of 85 to 95°C to perform first-stage micro-stretching, second-stage micro-stretching and third-stage micro-stretching on the second intermediate film material that has undergone three-stage stepped preheating, and the stretching ratio of the first-stage micro-stretching is 1.1 to 1.2, the stretching ratio of the second-stage micro-stretching is 1.2 to 1.5, and the stretching ratio of the third-stage micro-stretching is 1.5 to 1.

8.

8. The method for preparing a low-weight leakage-proof PE film according to claim 5, characterized in that: In step S2, the temperature of the casting steel roller and the casting pressure roller are both 20-28°C, and the mutual pressing force between the casting steel roller and the casting pressure roller is 4-6 kg / cm 2 .

9. The method for preparing a low-weight anti-leakage PE film according to claim 5, characterized in that: In step S4, the corona current of the corona treatment is 3-5A.

10. The method for preparing a low-weight anti-leakage PE film according to claim 5, characterized in that: In step S3, the water vapor permeability of the low-weight anti-leakage PE film is ≥1500g / (㎡.24h), the transverse tensile strength is ≥2.5N / 25mm, the longitudinal tensile strength is ≥10N / 25mm, the transverse elongation at break is ≥200%, the longitudinal elongation at break is ≥150%, and the longitudinal heat shrinkage is 3-6%.

Citation Information

Patent Citations

  • Special WVTR (water vapour transmission rate) breathable film and production process thereof

    CN103496239A

  • Polyethylene composition for sanitary towel bottom film and preparation technology thereof

    CN107828108A

  • Special-performance breathable film and production process thereof

    CN108099148A

  • Polyethylene (PE) microporous breathable film for medical protective clothing and preparation method thereof

    CN111875864A

  • Anti-virus, high-moisture-permeability and single-sided antistatic film and preparation method thereof

    CN114750494A

Cited By

  • Base membrane material of paper diaper and preparation process of base membrane material

    CN121517806A